60.3k views
0 votes
Somebody please help with this question: 2x – 12 – 3x = 60​

User SkyRar
by
5.3k points

1 Answer

1 vote

Answer:

Step-by-step explanation:

The first step to solve this equation is to add like numbers: 2x and -3x can be added together. Just as 2 + (-3) is -1, 2x + (-3x) is -1x.

The equation is now -x - 12 = 60. Add 12 on both sides of the equation and you’ll get -x = 72

Because x has a negative 1 in front of it we cancel it out by multiplying negative 1 on both sides. (-1) (-1x) = 72 (-1)

This makes x = -72

User Renne Rocha
by
5.6k points